Effect of Co-presentation of Adhesive Ligands and Short Hyaluronan on Lymphendothelial Cells - Antoni, Christiane H.; McDuffie, Yvonne; Bauer, Jochen; Sleeman, Jonathan P.; Boehm, Heike (Frontiers in Bioengineering and Biotechnology, 2018)
Controlled activation of lymphangiogenesis through functional biomaterials represents a promising approach to support wound healing after surgical procedures, yet remains a challenge. In a synthetic biological approach, we therefore set out to mimic the basal microenvironment of human primary dermal lymphatic endothelial cells (LECs) during lymphangiogenesis. As the extracellular matrix component hyaluronan (HA) regulates lymphangiogenesis, we designed a bifunctional surface in which adhesive peptide ligands and short HA oligosaccharides (sHA) tethered to nanoparticles are co-presented to the basal side of LECs in a controlled, concentration dependent manner. Exposure of LECs to sHA in solution to mimic luminal stimulation of the cells did not result in modified metabolic activity. However, LECs grown on the bifunctional adhesive surfaces showed a biphasic change in metabolic activity, with increased metabolic activity being observed in response to increasing nanoparticle densities up to a maximum of 540 particles/ µm2. Thus, interfaces that concomitantly present adhesive ligands and sHA can stimulate LEC metabolism and might be able to trigger lymphangiogenesis.